2012
DOI: 10.1259/bjr/56737365
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound treatment of liver tumours: post-treatment MRI correlates well with intra-operative estimates of treatment volume

Abstract: Objectives: To assess the safety and feasibility of high-intensity focused ultrasound (HIFU) ablation of liver tumours and to determine whether post-operative MRI correlates with intra-operative imaging. Methods: 31 patients were recruited into two ethically approved clinical trials (median age 64; mean BMI 26 kg m 22). Patients with liver tumours (primary or metastatic) underwent a single HIFU treatment monitored using intra-operative Bmode ultrasound. Follow-up consisted of radiology and histology (surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 17 publications
1
61
0
Order By: Relevance
“…Forty-four studies reported on the clinical use of HIFU (7,(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) to treat liver lesions , while 19 series were found on HIFU treatment for pancreatic cancers (6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) and 4 studies included patients suffering from both liver and pancreatic cancers (74)(75)(76)(77), reporting on a total of 1,682 and 823 cases for the liver and pancreas, respectively. However, the real number of patients who benefited from HIFU treatment is much larger, since a recent review article from Zhou reported on over 3,000 cases of advanced pancreatic cancer treated with HIFU alone or in combination with chemotherapy (CHT) or radiotherapy (RT) (78).…”
Section: Study Selection and Level Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Forty-four studies reported on the clinical use of HIFU (7,(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) to treat liver lesions , while 19 series were found on HIFU treatment for pancreatic cancers (6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) and 4 studies included patients suffering from both liver and pancreatic cancers (74)(75)(76)(77), reporting on a total of 1,682 and 823 cases for the liver and pancreas, respectively. However, the real number of patients who benefited from HIFU treatment is much larger, since a recent review article from Zhou reported on over 3,000 cases of advanced pancreatic cancer treated with HIFU alone or in combination with chemotherapy (CHT) or radiotherapy (RT) (78).…”
Section: Study Selection and Level Of Evidencementioning
confidence: 99%
“…The most frequent complications were skin burns at the application sites and osteonecrosis of ribs or vertebra along the US pathway ( Tables 5,6). Post-HIFU pain was not assessed systematically and was reported in 17 studies (384 patients undergoing liver HIFU procedures) (7,12,(19)(20)(21)(22)24,26,28,29,32,39,41,45,49,54,75) and 6 studies (62 patients receiving HIFU for pancreatic malignancies) (56,59,62,70,71,75). In only a few of those trials, a semi-quantitative evaluation tool was used to report pain level, based on the analgesic requirements (mild = no analgesic; moderate = non-steroidal anti-inflammatory drugs; severe = required morphine) (7,19,20,24,39).…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIFU is most widely used to thermally ablate a variety of both benign and malignant tumors including uterine fibroids, prostate cancer, liver tumors, and other solid tumors that are accessible to ultrasound energy (3)(4)(5)(6). It has been shown that HIFU therapy improves survival rates in certain oncological applications and improves outcomes in the treatment of benign conditions (1,5).…”
mentioning
confidence: 99%
“…The results of a recent clinical trial of transcranial HIFU for the successful treatment of essential tremor in 15 patients is an incredible milestone demonstrating the potential of this technology (7). HIFU targeting is usually performed by using either magnetic resonance (MR) imaging or B-mode ultrasound imaging (3,8). Neither method allows for direct visualization of the treated volume; however, MR thermometry is capable of providing tissue temperature maps during treatment, which can be correlated to the thermal dose and permits the ablated tissue volume to be calculated.…”
mentioning
confidence: 99%